Xpert Carba-R assay for detection of carbapenemase-producing organisms in patients admitted to emergency rooms. Issue 50 (11th December 2020) - Jin, Sol; Lee, Jin Young; Park, Ji Young; Jeon, Min Ji
Abstract : Abstract: Carbapenemase-producing organisms (CPO) have been identified as an urgent healthcare threat. Various methods have been used for the detection of CPO using rectal swabs. Recently, an on-demand polymerase chain reaction (PCR) assay, namely, the Xpert Carba-R assay, that requires less than an hour of turnaround time, had been developed for CPO detection in clinical samples. This study focused on the use of this assay to determine the intestinal colonization rate of CPO in patients admitted to emergency rooms (ERs). A retrospective review of medical records was conducted at a tertiary hospital between July 2017 and June 2018. CPO screening using rectal swabs was performed for patients transferred from other hospitals or for those who tested positive in CPO culture tests in the previous three months. The Xpert Carba-R assay and culture tests were used as the CPO screening methods, and the results of both tests were compared. Medical records of 705 patients admitted to our hospital during the study period were reviewed. Of these, 31 (4.4%) showed positive results for CPO using the Xpert Carba-R assay, and these patients were then transferred from the ERs to isolation rooms. Fifteen of the Xpert Carba-R assay-positive patients were also positive for the culture test; hence, early detection enabled the rapid isolation of CPO-infected patients and prevented the spread of the CPO. The Xpert Carba-R assay is a rapid test to identify and guide infection control programs to contain the spread of the rectal colonization of CPO within a hospital.